Knowledge management and academic performance: An empirical study of Iraqi HEIs - Zwain, Ammar A. Ali; Lim, Kong Teong; Othman, Siti Norezam (2012)
This study examines the relationship between the processes of Knowledge Management (KM) and educational organization outcome in respect to academic performance.The study is based on a survey design and cross-sectional.The survey was conducted on 41 quality improvement-adoption colleges in Iraqi higher-education institutions (HEIs).The study hypotheses were tested through correlation and regression analyses.The results supported the main hypotheses for the study, suggesting that Iraqi HEIs can benefit from KM processes. Pearson's correlation pointed out that all processes of KM have significant correlations with academic performance measures. Regression analysis showed significantly positive relationships.In addition, statistical analysis also indicated that the KM processes should be implemented collectively rather than separately.In conclusion, this study provided insight and further understanding of the effect of KM processes on academic performance, and therefore, allows decision-makers to get in-depth knowledge about the impact of KM processes in Iraqi HEIs context.